KAJIAN PEMANFAATAN LIMBAH NILAM UNTUK PUPUK CAIR ORGANIK DENGAN PROSES FERMENTASI - Soraya Santi, Sintha (Jurnal Teknik Kimia, 2010)
Waste of the distillation of pogestemon cablin still havet high nutrient content andpotential as a good raw material of organic fertilizer . Rapid composting technology and efficientorganic fertilizer will produce high quality compost. This study aim to determine the bestconditions in terms of fermentation time 6,10,14,18,22 day and volume of bacteria (EM4):2,4,8,10% EM4/solution were added to the N, P, K most in the process of making liquid fertilizerto use waste leaves the distillation of pogestemon cablin of N, P and K respectively 10.6% weight,1.19% and 3.08% heavy weight and the volume EM4 8% and the fermentation time of 14 days.Key words : pogestemon cablin, fermentation, ,liquid organic fertilizer, nitrogen,kalium, phospor